Trapezoidal dual loop antenna for Radio Frequency Identification (RFID) system at low frequency - Mansap, Chawanthawat; Wounchoum, Phairote; Phongcharoenpanich, Chuwong; Torrungrueng, Danai (My University, 2006)
This paper proposes the trapezoidal dual loop antenna for radio frequency identification (RFID) system at low frequency band (125 kHz and 134.2 kHz). Typically, the conventional antenna for this system is the rectangular loop. The antenna structure is simple at the expense of limited tag orientation and shorter distance communications. The advantage of the proposed antenna is that it can be used for arbitrary orientation with the further distance. It also possesses the simple structure with low cost. The simulation is carried out by using the Numerical Electromagnetic Code (NEC) to determine the suitable parameters. The antenna prototype is fabricated and measured to validate the antenna design and performance in RFID system. Copyright 2006 IEICE.
Keywords: Radio frequency identification (RFID); Trapezoidal dual loop antenna